FACTORS OF DEVELOPMENT OF PUBLIC-PRIVATE PARTNERSHIP IN VOCATIONAL EDUCATION INSTITUTIONS OF THE CONSTRUCTION INDUSTRY (Innovative professional education, 2025)
The article identifies the factors of development of public-private partnerships in vocational education institutions, which are the basis for the organizational and pedagogical conditions for the development of public-private partnership projects in the construction industry. The features of the construction industry that affect the system of scientific, methodological, pedagogical, organizational and practical measures aimed at the formation and application of the competencies of students necessary for professional activity are characterized
Keywords: public-private partnership, vocational education institutions, skilled workers, construction industry